2019
DOI: 10.1111/ede.12281
|View full text |Cite
|
Sign up to set email alerts
|

sRNA‐pathway genes regulating myxobacterial development exhibit clade‐specific evolution

Abstract: Small non-coding RNAs (sRNAs) control bacterial gene expression involved in a wide range of important cellular processes. In the highly social bacterium Myxococcus xanthus, the sRNA Pxr prevents multicellular fruiting-body development when nutrients are abundant. Pxr was discovered from the evolution of a developmentally defective strain (OC) into a developmentally proficient strain (PX). In OC, Pxr is constitutively expressed and blocks development even during starvation. In PX, one mutation deactivates Pxr a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 66 publications
0
11
0
Order By: Relevance
“…Therefore, undergoing development while nutrients are still abundant would seem undesirable. Previous work from our group has identified several genes that regulate the transition to development, all of which appear to belong to the same regulatory pathway controlled by the small RNA Pxr ( Yu et al, 2010 , 2016 ; Chen et al, 2019 ). In this study, we identify a mutation in the universal bacterial transcription machinery gene rpoB that impacts the M. xanthus developmental response to nutrients, a connection not revealed by mutations previously known to confer RM development.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, undergoing development while nutrients are still abundant would seem undesirable. Previous work from our group has identified several genes that regulate the transition to development, all of which appear to belong to the same regulatory pathway controlled by the small RNA Pxr ( Yu et al, 2010 , 2016 ; Chen et al, 2019 ). In this study, we identify a mutation in the universal bacterial transcription machinery gene rpoB that impacts the M. xanthus developmental response to nutrients, a connection not revealed by mutations previously known to confer RM development.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study found that the suppressor strain OC::TnE1 was able to form sporebearing fruiting bodies despite its parental strain's developmental defect [26]. Figure 2 shows the defect of the parental strain OC compared to the restored ability of OC::TnE1 to form fruiting bodies.…”
Section: The Tne1 Insertion In Rnd Restores Developmental Proficiencymentioning
confidence: 97%
“…OC is unable to eliminate Pxr-S in response to starvation [22] and is therefore deficient in starvation-induced fruiting-body formation in pure culture. OC::TnE1 was found by screening a transposon-mutant library for restored developmental proficiency and has a transposon inserted in the gene MXAN_5981 (rnd), a Ribonuclease D homolog [26]. GJV1::TnE1 and OC::TnE1-r were constructed by transforming a fresh growing strain of GJV1 and GVB207.3, respectively, with ~500 ng of OC::TnE1 genomic DNA and plated on CTT-kanamycin to select for clones resulting from a double crossover at the homologous regions flanking the transposon interstation site.…”
Section: Strainsmentioning
confidence: 99%
See 2 more Smart Citations